(untitled) (Research, Society and Development, 2022)
Mucoepidermoid carcinoma is the most common malignant salivary gland tumor in the oral cavity and affects mainly the parotid gland. Regarding its epidemiology, the incidence of MSC is higher in females and the mean age of patients is 45 years with a peak between the 4th and 6th decades of life. The clinical behavior of MSC is highly variable, ranging from indolent tumor growth to highly aggressive metastatic spread. However, the prognosis will depend considerably on the clinical stage of the lesion, its anatomical location, the histopathological grade and the treatment adopted. Given this, the objective of this study was to discuss the importance of the role of the dentist in the early diagnosis of mucoepidermoid carcinoma in the parotid gland and the result in the prognosis. As for the methodology used, it consists of a narrative literature review, through a search in Google Academic, Scielo, BVS, PUBMED. The diagnostic method is done through palpation, but as there are several differential diagnoses, it is essential that an incisional biopsy is performed for histopathological analysis. It was found that the participation of dentists brought several benefits related to the prognosis of patients with mucoepidermoid carcinoma, due to the possibility of metastasis or the simple fact that it is a malignant tumor and compromises the parotid gland, the dentist’s role in diagnosing clinical signs early is essential for a favorable prognosis.